Cover Image, Volume 232, Number 9, September 2017. Issue 9 (September 2017) - Poli, Alessandro; Fiume, Roberta; Baldanzi, Gianluca; Capello, Daniela; Ratti, Stefano; Gesi, Marco; Manzoli, Lucia; Graziani, Andrea; Suh, Pann‐Ghill; Cocco, Lucio; Follo, Matilde Y.
Abstract : Cover : The cover image, by Alessandro Poli et al., is based on the Original Research Article Nuclear Localization of Diacylglycerol Kinase Alpha in K562 Cells Is Involved in Cell Cycle Progression, DOI:10.1002/jcp.25642 .